The lost boys ebook A decker/lazarus novel. - Kellerman, Faye (Peter Decker/Rina Lazarus, 2021)
Faye Kellerman returns with an atmospheric, fast-paced mystery set in bucolic upstate New York, full of unexpected twists and turns that build to a shocking and surprising end—the latest thrilling entry in her New York Times bestseller Decker/Lazarus series. When Bertram Lanz goes missing from a local diner near Greenbury, the entire community of the small upstate New York town volunteers to search the surrounding woods. Bertram had been on a field trip with the staff and fellow residents of the Loving Care Home when he vanished. When no trace of the man is found, the disappearance quickly becomes an official missing persons case and is assigned to detectives Peter Decker and his partner Tyler McAdams. As their investigation deepens, the seasoned Decker becomes convinced that Bertram hadn't lost his way but must have left with someone he knew. Soon Decker discovers that Elsie Schulung, a recently fired nurse who had worked at the home, seemed to be especially interested in Bertram. But answers prove elusive when Elsie disappears and human blood is found in her kitchen. These complications prove to be only the beginning. While combing the woods, searchers discover the remains of one of three young men who had vanished during a camping trip. And for Decker, personal problems are adding pressure as well. After a ten-year absence, the biological mother of Decker and Rina's foster son, Gabriel, has suddenly appeared in New York, children in tow, wreaking emotional havoc on the young man. Juggling the personal and professional, a hot case and a cold case, Decker and McAdams race to find answers, sifting through cabinets of old files, a plethora of clues and evidence, and discouraging dead ends. As ongoing searches for Bertram and the campers' missing remains continue, the frustrated detectives begin to wonder if the woods will ever give up its dark secrets...